The Effect of Natural Sugar Substitute on the Physicochemical Indices of Cupcake - Hovhannisyan, N. G.; Khanamiryan, K. S. (ՀԱԱՀ հիմնադրամ)
Most of the sugar substitutes differ from each other in chemical composition, ways of their production, exerted effect on the metabolism of organism, as well as in their assimilability. The main goal of the current research is to develop a recipe for new functional food product by applying alternative natural sugar substitute. The extract produced from the licorice roots has been used as a natural substitute. The recommended product range is a single type of food product in the domestic market of functional foods and can stimulate the development of the mentioned branch.
Keywords: Food Science and Technology